The impact of leisure activities on the subjective well-being trajectory of Chinese residents: an 11-year longitudinal study - Wang, Guoqing; Sabran, Kamal; Wang, Yipei; Yu, Yang; Huang, Li; Li, Jian (Springer Nature, 2026)
Even though a great deal of attention has been paid to subjective well-being (SWB) as an important indicator of quality of life, it remains unclear how leisure activities exert long lasting influences on the development of SWB among residents in China. This study employs nationally representative sample data from the Chinese General Social Survey (CGSS) from 2010 to 2021, which covers 32 provincial administrative units. The final analysis contained 10,477 valid samples. We employed Latent class growth analysis (LCGA) to identify SWB trajectories and used binomial logistic regression to analyze the impact of 12 leisure activities, controlling for demographic variables and conducting stratified analysis and interaction effect tests for age, gender, and education level. The study identified two SWB trajectories: an initial low-level rising group (from 1.78 points in 2010 to 4.21 points in 2021) and a high-level stable group (always remaining around 3.9 points). Watching TV or DVDs, watching movies, listening to music, and surfing the Internet significantly affected the trajectory of SWB. Young people benefited most from Internet activities, while older people mainly benefited from watching TV or DVDs and Listening to music at home. Women and low-educated people benefit more widely from leisure activities (TV or DVDs, Movies, Music, Internet), and high-educated people mainly benefit from watching movies. A significant interaction existed between age and Internet activities. Leisure activities significantly affected the development trajectory of SWB of Chinese residents, especially for the initial low-level rising group. After 2018, the SWB of the initial low-level rising group exceeded that of the high-level stable group, indicating that the long-term cumulative effect of leisure activities is gradually emerging. These findings underscore the long-term cumulative effect of leisure activities on subjective well-being and highlight the need for targeted strategies that consider demographic differences to promote sustained SWB among Chinese residents.